Problematika Bahasa Indonesia Mahasiswa Asing: Analisis SVO Noam Chomsky pada Teks WhatsApp Mahasiswa Thailand di UIN Raden Mas Said Surakarta: Problems of Indonesian Language for Foreign Students: Noam Chomsky's SVO Analysis of WhatsApp Texts of Thai Students at UIN Raden Mas Said Surakarta - Dilfam Aldisya; Isnaini Nurul Firdaus; Shiffa Primadita Annisa; Siti Nurjanah (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
This study aims to identify SVO pattern sentences that have undergone structural transformation found in WhatsApp texts of Thai students at UIN Raden Mas Said Surakarta and compare them with native Indonesian students. This study is based on the generative syntax approach developed by Noam Chomsky. The results of the study show that sentence patterns that appear such as ellipsis, use of abbreviations, and incomplete sentences are characteristic of language use, with the dominant S-V-O, S-V, and V-S syntactic patterns. Southern Thai Malay shows greater flexibility in the application of existential structures and elliptical forms than Indonesian. Meanwhile, Indonesian is more loyal to standard and adaptive structures, such as simplifying structures and eliminating elements that are considered unimportant in the digital context. However, both languages ​​maintain the S-V-O pattern as the main syntactic basis. This shows that digital communication encourages a shift from rigid syntactic norms to more flexible and functional structures.